Substance use, mental health and weight‐related behaviours during the COVID‐19 pandemic in people with obesity. Issue 2 (4th February 2021) - Almandoz, Jaime P.; Xie, Luyu; Schellinger, Jeffrey N.; Mathew, M. Sunil; Bismar, Nora; Ofori, Ashley; Kukreja, Sachin; Schneider, Benjamin; Vidot, Denise; Messiah, Sarah E.
Summary: Studies have shown the negative impact of COVID‐19 lockdown orders on mental health and substance use in the general population. The aim of this study was to examine the impact of the COVID‐19 pandemic onsubstance use, mental health and weight‐related behaviors in a sample of adults with obesity after lockdown orders were lifted (June‐September 2020). A retrospective medical chart review identified patients with obesity from one university‐based obesity medicine clinic, and two metabolic and bariatric surgery (MBS) practices. Patients who completed an online survey from June 1, 2020 to September 30, 2020 were included. The primary outcome measure was substance use (various drugs, alcohol, tobacco). Substance use and mental health survey questions were based on standardized, validated instruments. A total of 589 patients (83.3% female, mean age 53.6 years [SD 12.8], mean BMI 35.4 [SD 9.1], 54.5% Non‐Hispanic white, 22.3% post‐MBS) were included. Seventeen patients (2.9%) tested positive for SARS‐CoV‐2 and 13.5% reported symptoms. Nearly half (48.4%) of the sample reported recreational substance use and 9.8% reported increased use since the start of the pandemic. There was substantial drug use reported (24.3% opioids, 9.5% sedative/tranquilizers, 3.6% marijuana, and 1% stimulants). Patients who reported stockpiling food more (adjusted Odds Ratio [aOR] 1.50, 95% CI 1.03‐2.18), healthy eating more challenging (aOR 1.47, 95% CI 1.01‐2.16), difficulty falling asleep (aOR 1.64, 95% CI 1.14‐2.34), and anxiety (aOR 1.47, 95% CI 1.01‐2.14) were more likely to report substance use versus non‐users. Results here show that the COVID‐19 pandemic is having a deleterious impact on substance use, mental health and weight‐related health behaviors in people with obesity regardless of infection status.